Epidermal Acidification and Skin Barrier Optimization in the Management of Atopic Dermatitis: A Series of Three Cases Successfully Managed by a Novel Approach. Issue 5 (September 2016) - Pham, Quy; Eberting, Cheryl Lee
Abstract : ABSTRACT: The importance of the epidermal acid mantle in maintaining the natural flora of the skin and its role in skin barrier homeostasis has been known for decades. Despite well-established evidence that the skin barrier pH is elevated in patients with inflammatory dermatoses such as atopic dermatitis, epidermal pH modification has been an underexplored therapeutic option that could potentially prevent overuse of antibiotics, topical glucocorticoids, and immune modulators. By optimizing the skin using a novel therapeutic regimen, we report three cases of recalcitrant atopic dermatitis that were successfully treated based on the concept of epidermal acidification combined with optimization of the skin barrier.